Living with African Bees in Florida's Outdoor Workplaces - Michael K. O'Malley; James D. Ellis (EDIS)
ENY-146, a 5-page illustrated fact sheet by M. K. O’Malley and J. D. Ellis, offers African honey bee related recommendations and precautions specific to outdoor workers in Florida. Includes additional resources. Published by the UF Department of Entomology and Nematology, June 2008.